2003
DOI: 10.1111/j.1745-459x.2003.tb00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Structured and Unstructured 9‐point Hedonic Scales: A Cross Cultural Study With American, Japanese and Korean Consumers

Abstract: The range of scores elicited by a structured, an unstructured and a 'labelsonly' version of the 9-point hedonic scale were compared using consumersfrom USA, Japan and Korea. It was found that the unstructured scale elicited a wider range of scores for American and Japanese consumers. Afrer correction for hedonic ranges, it was found that Japanese had smaller ranges of scores on all three scales, although the effect was less pronounced for the unstructured scale. The Korean consumers were the exception. Their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 42 publications
4
52
0
Order By: Relevance
“…This scale is reported to show some advantages over the 9-point scale (Villanueva & Da Silva, 2009;Villanueva et al, 2005). Yao et al (2003) found wider scale usage with an ''unstructured" 9-point category scale with only numbered boxes and no phrases attached. One way to potentially remove the categorical behavior with the LAM scale would be to strip off the interior labels entirely.…”
Section: Discussionmentioning
confidence: 95%
“…This scale is reported to show some advantages over the 9-point scale (Villanueva & Da Silva, 2009;Villanueva et al, 2005). Yao et al (2003) found wider scale usage with an ''unstructured" 9-point category scale with only numbered boxes and no phrases attached. One way to potentially remove the categorical behavior with the LAM scale would be to strip off the interior labels entirely.…”
Section: Discussionmentioning
confidence: 95%
“…These include end effects, centering biases, and stimulus-spacing biases. It has been reported that when closeended scales such as category and line scales are employed, the end points of the scales are used less frequently than other parts of the scale (i.e., end effects) (Anderson, 1974;Eriksen & Hake, 1957;Moskowitz, 1982;Schifferstein & Frijters, 1992;Stevens & Galanter, 1957;Yao et al, 2003;Yeh et al, 1998). Because subjects must consider the possibility that a better or worse (or stronger or weaker) stimulus may be presented later in the test, they are often reluctant to use the end points.…”
Section: Other Context Effectsmentioning
confidence: 97%
“…Whatever translation and wording is used, the accuracy of translation may remain difficult to evaluate (cf. Yao et al, 2003;Yeh et al, 1998). Furthermore, when applied on the ratings of regular well-liked foods, the ''dislike" categories from 1 to 4 have little use and thus, the scale may truncate into a 5-point scale from ''do not dislike nor like" to ''like extremely".…”
Section: Introductionmentioning
confidence: 98%